Revealing the reproducibility and coordination of highly-skilled baseball throwing. - Kimura, Arata; Nakashima, Hirotaka (Journal of Sports Sciences, 2025)
There has been interest in identifying the key factors for exceptional sports performance. One possible approach to addressing this issue is to focus on coordination and numerous studies have empirically examined coordination. In our study, we demonstrated the coordination exhibited by high-skilled athletes but not by novices during a throwing task. Participants alternated between overhead and sidearm throws to a target, and the positional data of reflective markers attached to the baseball were captured using a motion capture system. Our findings revealed that high-skilled athletes coordinated the ball release position in the left-right direction with the azimuth angle of the translational ball velocity, thereby minimising the variability in the ball arrival position. Similarly, high-skilled athletes also coordinated the ball release position in the upward-downward direction with the elevation angle of the translational velocity. The coordination was not exhibited by the novices. Furthermore, it was observed that high-skilled athletes reduced variability in the ball arrival position by minimising variability of both the azimuth and elevation angles of the translational ball velocity. Our study identifies key differences between high-skilled athletes and novices during the throwing task and offers valuable insights for advancing the understanding of sports skills.